2016
DOI: 10.21608/ejfsat.2016.41020
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of the Mandible in Egyptian Population Sample: A Panoramic Radiographic Study

Abstract: Sex determination is a crucial issue and is usually the first step in the process of identification in forensic investigations. However, it remains a very challenging task. The aim of this study was to determine the validity of radiographic measurements, from the superior and inferior borders of the mental foramen to the lower border of the mandible (S-L and I-L), and from the medial margin of the mental foramen to the mandibular symphisis (MF -MS) on both right and left sides of the mandible, in sex determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…17 Elgazzar et al in 2016 in Egyptian population found sexual dimorphism in the position of mental foramen. 18 Rodriguez Cardenar YA in 2018 studied the distance of lower border of mental foramen to base of mandible in Peruvian subjects and found the measurements were found to be greater in males. 19 Rani A et al in 2019 studied the position of mental foramen in West Bengal population and found results similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…17 Elgazzar et al in 2016 in Egyptian population found sexual dimorphism in the position of mental foramen. 18 Rodriguez Cardenar YA in 2018 studied the distance of lower border of mental foramen to base of mandible in Peruvian subjects and found the measurements were found to be greater in males. 19 Rani A et al in 2019 studied the position of mental foramen in West Bengal population and found results similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Different populations have variable anatomical features which attributed to different sexual characteristics, therefore it is necessary to investigate each populationrelated standard (Elgazzar et al, 2016), up to our knowledge there are not any similar studies investigated using MDCT imaging of palate in sex determination in Egyptian population, so this study is aimed toward analysis of palatine MDCT imaging for sexual dimorphism in a sample from Egyptian population.…”
Section: Introductionmentioning
confidence: 99%